Social Media Tools and Platforms in Learning Environments - White, Bebo.; King, Irwin; Tsang, Philip; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Online social media have transformed the face of human interaction in the 21st century. Wikis, blogs, online groups and forums, podcasts, virtual worlds, and social tagging are but a few of the applications enabling innovative behaviors that support acquisition, access, manipulation, retrieval, and visualization of information. It is, therefore, no surprise that educational practitioners and theorists have begun to explore how social media can be harnessed to describe and implement new paradigms for communication, learning, and education. The editors goal in publishing this book was to identify original research on the application of online social media and related technologies in education as well as emerging applications in Web technologies that could provide and shape future educational platforms. The selected contributions deal with questions such as how social media can truly enrich and enhance learning and teaching experiences in ways not otherwise possible; how learning can be integrated in a distributed and ubiquitous social computing environment; or what theories, paradigms, and models are applicable for the support of social computing in education. Researchers in education or educational software will find interesting and sometimes provocative chapters on paradigms and methodologies, virtual and mobile learning spaces, and assessment and social factors. Practitioners in these fields will benefit from an additional section devoted to case studies and first experience reports.
Revitalize Your Teaching: Creative Approaches to Applying Social Media in the Classroom -- Teaching and Learning in a Social Software Development Tool -- Collective Learning ? An Integrated Use of Social Media in Learning Environment -- New Learning Paradigms. Open Course Versus Traditional Strategies. The Current Paradox of Learning and Developing Creative Ideas -- States and Processes of Learning Communities. Engaging Students in Meaningful Reflection and Learning -- How to Foster Creativity in Technology Enhanced Learning? -- Exploiting Geocollaborative Portals for Designing Collaborative e-Learning Pedagogies: a Model, Applications and Trends -- Building Institutional Capacity for the Use of Social Media -- Leadership within Virtual Environments: Do Physical Characteristics Matter -- Virtual Worlds: Spaces for Education or Places for Play -- Social-Network Tools for the Assessment of the University Web Performance -- Social Capital in Electronic Networks of Practice: an Analysis of University Blogging Communities -- Understanding Online Sociability: Investigations on Sociability Determinants and Cultural Differences in Sociability Perception -- Using Social Media to Empower Learning Resources Evaluation and Recommendation across Boundaries -- Multimodality and Context-adaptation for Mobile Learning -- Context-Sensitive Content Representation for Mobile Learning -- Progressing the Social Dimension towards the Collaborative Construction of Knowledge in 2.0 Learning Environments. A Pedagogical Approach -- Contributions to Social Bookmarking Systems: Integration of Three Empirical Studies -- The Role of Social Presence in Interactive Learning with Social Software -- Visualising Social Computing Output: Mapping Student Blogs and Tweets -- Learning from Medical Social Media Data: Current State and Future Challenges -- Sampling the Sea: Using Social Media for an Online Ocean Sustainability Curriculum -- ASK-LOST 2.0: A Web-Based Tool for Social Tagging Digital Educational Resources in Learning Environments -- Learning in the Digital Age with SNSs: Creating a Profile -- myLearningSpace: Engaging Education.
Electronic reproduction.
Keywords: Educational technology; Educational Technology; Aufsatzsammlung; Internet; Lernumwelt; Neue Medien; Electronic books